Regulatory CD4+CD25+ cells reverse imbalances in the T cell pool of bone marrow transplanted TGε26 mice leading to the prevention of colitis. (11th January 2005) - Veltkamp, C; Sartor, R B; Giese, T; Autschbach, F; Kaden, I; Veltkamp, R; Rost, D; Kallinowski, B; Stremmel, W
Abstract : Background and aims: Erroneous thymic selection of developing T lymphocytes may be responsible for the expansion of self reactive T cells or may contribute to the absence of regulatory T cells important in controlling peripheral inflammatory processes. Colitis in bone marrow (BM) transplanted Tgε26 mice is induced by abnormally activated T cells developing in an aberrant thymic microenvironment. We investigated the protective role of regulatory CD4 + CD25 + T cells in this model. Methods: BM from (C57BL/6×CBA/J) F1 mice was transplanted into specific pathogen free Tgε26 mice (BM⇒Tgε26). Transplanted mice received no cells (control), sorted CD4 + CD25 +, or CD4 + CD25 − cells from mesenteric lymph nodes (MLN) of normal mice. MLN cell subsets were analysed using membrane markers. Cytokine secretion of MLN cells was measured using intracellular cytokine staining and cytokine secretion in anti-CD3 stimulated cell cultures. Colitis was measured by histological scores. Results: CD4 + CD25 + cells were reduced in the MLNs of BM⇒Tgε26 mice. Transfer of regulatory CD4 + CD25 + but not of CD4 + CD25 − cells reduced the number of MLN CD4 + T cells in BM⇒Tgε26 recipients and increased the number of MLN CD8 + cells, thereby normalising the CD4 + /CD8 + ratio. CD4 + CD25 + but not CD4 + CD25 − cell transfer into BM⇒Tgε26 mice reduced the number of tumour necrosis factor α + CD4 + cells and increased the secretion of transforming growth factor β by MLN cells. Transfer of 3×10 5 CD4 + CD25 + cells after BM transplantation into Tgε26 mice prevented colitis whereas CD4 + CD25 − cells had no protective effect. Conclusions: These results suggest that defective selection or induction of regulatory T cells in the abnormal thymus is responsible for the development of colitis in BM⇒Tgε26 mice. Transfer of CD4 + CD25 + cells can control intestinal inflammation in BM⇒Tgε26 mice by normalising the number and function of the MLN T cell pool.